Ethical leadership in a complex environment: A case study on Nunavik health organizations. Issue 2 (17th January 2023) - Morin, Geneviève; Talbot, David
Abstract: Despite being the primary homeland of Quebec's Inuit people, Nunavik's health care is typically planned and provided by non‐Inuit newcomers. This retrospective case study investigates the effects of ethical leadership on the Westernized local Nunavik health care system's cultural sensitivity to its disproportionately Inuit populations. An integrative framework is developed that considers the dimensions of ethical leadership and the omnibus and discrete dimensions of context. This study shows that some Nunavik health care managers seek to improve and adapt the system to the needs of their Inuit populations, while others do not. Unfortunately, the context restricts the former managers' ability to act consistently with their moral responsibilities and beliefs. Specifically, the findings show various institutional barriers to providing respectful and sensitive health care to Inuit. This study contributes to the scientific literature on ethical leadership by proposing an integrative conceptual framework. This framework illustrates how ethical leadership is inseparable from organizational context, identifying 16 contextual factors influencing managers' ethical behavior. Finally, three practical recommendations are proposed to highlight the omnibus and discrete context elements.